Retinal imaging in Angiomatous Retinae - Deeksha Singh; Anamika Nath; Divya Swamyraj (Delhi Journal of Ophthalmology)
The present report aims to describe the use of multimodal imaging in a rare case of Angiomatous Retinae which helps in its diagnosis, prognosis and plan management.